A missense mutation in the Sin3 subunit of Rpd3 histone deacetylase complex bypasses the requirement for FNG1 in wheat scab fungus - Huaijian Xu; Ruoxuan Jiang; Xianhui Fu; Qinhu Wang; Yutong Shi; Xiaofei Zhao; Cong Jiang; Hang Jiang (Journal of Integrative Agriculture)
The Rpd3 histone deacetylase complex is a multiple-subunit complex that mediates the regulation of chromatin accessibility and gene expression. Sin3, the largest subunit of Rpd3 complex, is conserved in a broad range of eukaryotes. Despite being a molecular scaffold for complex assembly, the functional sites and mechanism of action of Sin3 remain unexplored. In this study, we functionally characterized a glutamate residue (E810) in FgSin3, the ortholog of yeast Sin3 in Fusarium graminearum (known as wheat scab fungus). Our findings indicate that E810 was important for the functions of FgSin3 in regulating vegetative growth, sexual reproduction, wheat infection, and DON biosynthesis. Furthermore, the E810K missense mutation restored the reduced H4 acetylation caused by the deletion of FNG1, the ortholog of the human inhibitor of growth (ING1) gene in F. graminearum. Correspondingly, the defects of the fng1 mutant were also partially rescued by the E810K mutation in FgSin3. Sequence alignment and evolutionary analysis revealed that E810 residue is well-conserved in fungi, animals, and plants. Based on Alphafold2 structure modeling, E810 localized on the FgRpd3–FgSin3 interface for the formation of a hydrogen bond with FgRpd3. Mutation of E810 disrupts the hydrogen bond and likely affects the FgRpd3–FgSin3 interaction. Taken together, E810 of FgSin3 is functionally associated with Fng1 in the regulation of H4 acetylation and related biological processes, probably by affecting the assembly of the Rpd3 complex.